Penerapan Metode ROC Dan Metode WASPAS Untuk Menentukan Penerima Beasiswa KIP Kuliah - Muhammad Syahrizal; Soeb Aripin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
KIP lectures are lecture education assistance which aims to free registration for college entrance selection and tuition or education fees. One of the tertiary institutions that has the opportunity to get KIP Lectures is Budi Darma University. Based on the results of observations and interviews with the assistant head of student affairs at Budi Darma University to determine the feasibility of the Indonesia Smart Card (KIP) College scholarship currently still using the conventional election system, by means of students submitting files to the selection team for the Indonesia Smart Card (KIP) College scholarship then taking part in tests and interviews To overcome the problems experienced by the selection team, a system is needed to help the selection team. One of them is using the Decision Making System (SPK). Where to do a combination of the Decision Support System method with the ROC method used for weighting and the WASPAS method used for alternative rankings. With the aim of providing recommendations for students who get KIP college scholarships. From the results of the calculation of the values ​​above, it can be determined who will receive the KIP College scholarship based on recommendations from the decision support system by applying the ROC method which is used as weighting and the WASPAS method which is used as a ranking determination to get the best ranking results on behalf of Iramaya Tampubolon with a Qi value of 0. 991921266, it can be concluded that if KIP quotas study at Budi Darma University 10, the ranking taken is according to the number of cities received.